A COMPARATIVE STUDY ABOUT THE AMOUNT OF MICROPLASTIC IN POLYETHYLENE TEREPHTALATE (PET) DRINKING WATER THAT WAS EXPOSED AND NOT EXPOSED BY SUN AT ENVIRONMENTAL HEALTH LABORATORY OF POLTEKKES KEMENKES SEMARANG AT THE YEAR 2020 - Atyaf Umi Faizah; Sugeng Abdullah; Budi Triyantoro; Febri Apwanti Kusumaningtyas (Poltekkes Kemenkes Semarang, 2020)
The majority of bottled water industry uses polyethylene terephthalate (PET) bottles as their packaging. When exposed to direct sunlight, this type of packaging is able to cause new compounds in water. Research at the State University of New York states showed that from 259 bottled water in 9 countries, 242 of them contained microplastics. The purpose of this study is to determine whether there are differences in the amount of microplastic in bottled PET containers that are exposed and not exposed to sunlight. This type of research is pre-experimental using the static group comparison design. There are 2 treatment groups: PET bottled water that is exposed and not exposed to sunlight. The results showed that there were microplastics in PET bottled water exposed and not exposed to sunlight. Samples of bottled PET which exposed to sunlight have microplastic’s number of 175 particles/ liter. Whereas bottled water that was not exposed to sunlight has microplastic’s number of 132,25 particles/ liter. Independent t-test showed that the Sig (2-tailed) value was 0,023. This value less than = 0,05. So, we can say that there were differences between both of them. The conclusion of the study was that there were differences in the number of microplastics between PET bottled water exposed and not exposed to sunlight. As a form of vigilance, the public is advised to deliver PET bottled water from direct sunlight both for distribution and other type utilization of PET bottles for other purposes such as disinfection of water using sunlight (SODIS).